Post-traumatic growth as positive personality change: developing a measure to assess within-person variability - Blackie, Laura E.R.; Jayawickreme, Eranda; Tsukayama, Eli; Forgeard, Marie, J.C.; Roepke, Ann Marie; Fleeson, William (Elsevier, 2016)
Earlier work has defined post-traumatic growth (PTG) as positive personality change, but measurement of this construct has relied almost exclusively on cross-sectional and retrospective assessments. The aim of this study was to use an experience-sampling procedure to measure the extent to which PTG manifested in individuals’ everyday lives after a recent highly stressful or traumatic adverse event (compared to a control group). In doing so, we developed a state measure of PTG. The factor structure of state PTG was comparable to trait PTG, there was significant variability in individuals’ PTG from moment-to-moment, but individuals’ trait PTG was unrelated to their state PTG. Moreover, individuals who had experienced a recent adversity did not differ from control participants on state PTG.